2018
DOI: 10.1177/0748233718817192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active and passive smoking on salivary cytokines levels in rats: A pilot study

Abstract: Cigarette smoking is an established risk factor for some oral diseases. As an essential fluid in the oral cavity, saliva is crucial to maintain oral health. Relative to active smoking, there are very few studies assessing the effect of passive smoking on salivary cytokines levels. In the present study, we established the rat models by the means of the intraoral cigarette smoking or whole body cigarette smoke exposure to simulate human active or passive smoking, respectively. The effects of active or passive sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…19,44 For instance in a study of the Qatari population's microbiome profile, 19 found that non-smokers exhibit significantly greater diversity in their salivary microbiome compared to smokers, as evidenced by alpha diversity measures. Moreover, smoking activates inflammatory cells and elevates systemic levels of various inflammatory markers, such as C-reactive protein, fibrinogen, and IL-6, 44,45 thus supporting the findings of our present study.…”
Section: Discussionsupporting
confidence: 91%
“…19,44 For instance in a study of the Qatari population's microbiome profile, 19 found that non-smokers exhibit significantly greater diversity in their salivary microbiome compared to smokers, as evidenced by alpha diversity measures. Moreover, smoking activates inflammatory cells and elevates systemic levels of various inflammatory markers, such as C-reactive protein, fibrinogen, and IL-6, 44,45 thus supporting the findings of our present study.…”
Section: Discussionsupporting
confidence: 91%
“…33 Multiple possible explanations might justify these differences; one is that nonsmoker patients may have been passive smokers through exposure from individuals who actively smoke; this may affect the results since there is a piece of evidence that passive smoking can activate proinflammatory cytokines. 34 Additionally, in this study, heavy cigarette smokers were exclusively included based on CDC definition criteria, which might be different from the criteria used by other studies. Additionally, tobacco smoking was selfreported in this study.…”
Section: Discussionmentioning
confidence: 99%